2020
DOI: 10.2147/ijn.s257741
|View full text |Cite
|
Sign up to set email alerts
|

<p>Cerium Oxide Nanoparticles Regulate Osteoclast Differentiation Bidirectionally by Modulating the Cellular Production of Reactive Oxygen Species</p>

Abstract: Background: Cerium oxide nanoparticles (CeO 2 NPs) are potent scavengers of cellular reactive oxygen species (ROS). Their antioxidant properties make CeO 2 NPs promising therapeutic agents for bone diseases and bone tissue engineering. However, the effects of CeO 2 NPs on intracellular ROS production in osteoclasts (OCs) are still unclear. Numerous studies have reported that intracellular ROS are essential for osteoclastogenesis. The aim of this study was to explore the effects of CeO 2 NPs on osteoclast diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
40
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…There has been conflicting literature about cerium oxide nanoparticles’ ability to induce radiosensitization, despite being a metal with a high z number, with some studies showing radiosensitizing abilities [ 37 , 50 , 51 , 52 ], including in breast cancer [ 53 ], while others reporting it as a radioprotector [ 54 , 55 , 56 ]. Moreover, reports on the subcellular distribution of unmodified CeO 2 nanoparticles also varied widely based on the type of cells: in neuronal stem cells, they were predominantly localized in membrane-bound structures and, to a lesser extent, were found free in the cytoplasm, with none detected in the nucleus or other structures [ 57 ]; in gastric cancer cells, they were reported to be localized in lysosomes and in no other parts of the cell [ 58 ]; in human keratinocyte cells, they were localized in mitochondria, lysosomes, and endoplasmic reticulum, as well as being abundant in the cytoplasm and the nucleus [ 59 ]; however, in bone marrow-derived macrophages, the CeO 2 nanoparticles entered the nucleus and were found to disrupt the integrity of the cell membrane and organelles [ 60 ]. Moreover, it has been reported that the subcellular location of the nanoceria affected their cytotoxicity profiles, with minimal toxicity observed when localized in the cytoplasm and exhibiting significant cytotoxicity when present in the lysosomal compartment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…There has been conflicting literature about cerium oxide nanoparticles’ ability to induce radiosensitization, despite being a metal with a high z number, with some studies showing radiosensitizing abilities [ 37 , 50 , 51 , 52 ], including in breast cancer [ 53 ], while others reporting it as a radioprotector [ 54 , 55 , 56 ]. Moreover, reports on the subcellular distribution of unmodified CeO 2 nanoparticles also varied widely based on the type of cells: in neuronal stem cells, they were predominantly localized in membrane-bound structures and, to a lesser extent, were found free in the cytoplasm, with none detected in the nucleus or other structures [ 57 ]; in gastric cancer cells, they were reported to be localized in lysosomes and in no other parts of the cell [ 58 ]; in human keratinocyte cells, they were localized in mitochondria, lysosomes, and endoplasmic reticulum, as well as being abundant in the cytoplasm and the nucleus [ 59 ]; however, in bone marrow-derived macrophages, the CeO 2 nanoparticles entered the nucleus and were found to disrupt the integrity of the cell membrane and organelles [ 60 ]. Moreover, it has been reported that the subcellular location of the nanoceria affected their cytotoxicity profiles, with minimal toxicity observed when localized in the cytoplasm and exhibiting significant cytotoxicity when present in the lysosomal compartment [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…RANKL-induced BMMs activate MAPK and NF-κB (nuclear factor kappa-light-chain-enhancer of activated B cells) signals and cause osteoclast differentiation. MAPK signal is induced by the phosphorylation of ERK, JNK, and P38 in RANKL-induced osteoclasts [ 41 ]. In the NF-κB pathway, IκBα inhibits the initiation of the NF-κB signal pathway.…”
Section: Discussionmentioning
confidence: 99%
“…However, IκBα is phosphorylated by RANKL. In other words, the phosphorylation of IκBα leads to osteoclast differentiation [ 40 , 41 , 42 ]. GNPs slightly inhibited RANKL-induced phosphorylation of ERK, JNK, IκBα, and p65, whereas SNP groups further inhibited the phosphorylation ( Figure 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Next, the effects of SOG treatment on osteoclast-mediated bone resorption and F-actin ring formation of osteoclasts were examined. It is acknowledged that the formation of well-de ned F-actin ring was indispensable for osteoclastic function 4 . Figure 2a showed that the number and size of F-actin rings were effectively diminished with the increase of the concentration of SOG.…”
Section: Sog Inhibited Rankl-induced Osteoclast Formationmentioning
confidence: 99%
“…Previous studies suggested that in ammation and oxidative stress could promote osteoclast differentiation, leading to osteolysis 3,4 . Therefore, inhibition of excessive osteoclast formation and bone resorption activity has been regarded as an important therapeutic strategy for bone lysis diseases.…”
mentioning
confidence: 99%